A comparative study on banana seed systems in Mbarara district, western Uganda and Mukono district, central Uganda - Kilwinger, Fleur B.M.; Rietveld, Anne M.; Almekinders, Conny J.M. (International Potato Center, 2019)
Seed system interventions aim to provide farmers with clean, high yielding planting material. In order to make such interventions successful it is important to understand the traditional seed systems in which the interventions are made. This report describes the results of a comparative study between the banana seed system in Central and Western Uganda. These regions differ in cultivation history, production objectives and previous seed system intervention. These characteristics result in a difference in management practices, seed sourcing strategies and selection processes of banana planting material. In both areas, on-farm cultivar diversity is high, and maintained to fulfill multiple end-uses as well as to spread risk. In Central Uganda some cultivars are maintained due to cultural beliefs and their use in rituals. In the western region such motivations for cultivar maintenance were not mentioned. In Western Uganda farmers kept their banana mats small by regular de-suckering, which makes uprooting and replacing a mat easier. Selection of planting material in the western region is much focused on keeping existing mats healthy, whereas in the central region farmers focused mainly on the distinction between sword and water suckers. These insights into differences in preferences and motivations behind the selection of planting material and seed sourcing strategies can facilitate future seed system interventions and facilitate adaptation to farmers’ needs.